ANALISA LAPORAN KEUANGAN DITINJAU DARI SOLVABILITAS DAN LIKUIDITAS PADA PERUSAHAAN JASA TRANSPORTASI PT. EXPRESS TRANSINDO UTAMA, Tbk DAN PT. BLUE BIRD, Tbk PERIODE TAHUN 2015-2019 DALAM MENGHADAPI PANDEMI COVID-19 - Candra, Natasia Eno (Jurnal Kompetitif Bisnis, 2020)
Understanding the decisions made by companies that listed on the stock market today with the covid-19 pandemic wreaking havoc is very important, especially as an investor. This study determines the resilience and risk of bankruptcy using the solvency and liquidity ratios, in the transportation services sector company PT. Express Transindo Utama, Tbk (TAXI) and PT. Blue Bird, Tbk (BIRD) whose operating activities were reduced during this covid-19 pandemic. Analysis carried out using horizontal analysis in financial report the period of year 2015 to 2019. The results of the partial research show that the company’s decision to add debt has an effect on the increased risk of loss and bankruptcy that may be experienced by the company, especially if the decision taken by the company’s management had a high level of risk that will affect the company’s performance in dealing with the current covid-19 pandemic situation.